Nutritional Profile Of Promising Genotypes Of Buckwheat Grown In Dry Temperate Climatic Conditions Of Himachal Pradesh (India) (Applied Biological Research, 2014)
Buckwheat is economically important smaller millet grown primarily for  carbohydrate and protein content. In this study, biochemical  onstituents of 15 promising genotypes of buckwheat, grown in Sangla  region of Himachal Pradesh (India), were analyzed. The moisture, crude  protein, carbohydrate, fat, crude fibre and ash contents in genotypesranged from 10.0 to 11.7, 1.7 to 2.5, 1.7 to 2.5, 10.2 to 14.8, 1.8 to 2.9, 7.1  to 9.5 and 62.0 to 66.4%, respectively. The K, P, Mg, Ca, Fe and Zn  contents in buckwheat grains varied from 423 to 587.5, 248 to 370.2,  200.5 to 308, 43.7 to 58.03, 3.0 to 4.5 and 2.0 to 3.0 mg 100 g-1,  respectively. Based on cumulative grading of nutritionally desirable  qualities, the genotypes S-B-216 and Kamru followed by S-B-206 and  Chini proved superior cultivars.
Keywords: Biochemical constituents; buckwheat; genotypes; India; nutritional profile